PENGADAAN TEMPAT SAMPAH UNTUK MENINGKATKAN KEBERSIHAN LINGKUNGAN DESA PULAU PAYUNG RUMBIO JAYA - Harsanto Mursyid; Sarah Zahirni; Gracia Welly Ginting; Fahriadi '; Vivi Hersya; Fitri Amalia; Dzaky Zahran; Tri Dwi Anggita; Biefanza Rama; Nadia Harta (COMMENT: Journal of Community Empowerment, 2022)
The problem that is being faced by the world at this time is the waste problem, even in Indonesia itself it has not been resolved. Especially in Pulau Payung Village, which needs special attention regarding waste due to the crisis in the existence of trash bins, therefore the procurement of trash bins is carried out. The purpose of this activity is to increase public awareness about disposing of waste in its place so that the environment becomes cleaner and healthier. This activity consists of four stages, namely the preparation, implementation, final and evaluation stages. The evaluation was carried out by interviewing several resource persons involved in village management. The results of the service are considered quite good because they can encourage public awareness about cleanliness so that the environment becomes cleaner and healthier.